Morfologia e evolução em vespas parasitoides (Hymenoptera: Chalcididae: Chalcidinae) - Hoppe, Joao Paulo Maires (2020)
Parasitoids are organisms that exploit a single host, obtaining from him all the needed resources for survival and development, eventually resulting in the host death. Parasitoidism is an evolutionary strategy of great success, present in at least 10% of